The Retrograde Connections and Anatomical Segregation of the Göttingen Minipig Nucleus Accumbens - Meidahl, Anders C.; Orlowski, Dariusz; Sørensen, Jens C. H.; Bjarkam, Carsten R. (Frontiers in Neuroanatomy, 2016)
Nucleus accumbens (NAcc) has been implicated in several psychiatric disorders such as treatment resistant depression (TRD) and obsessive-compulsive disorder (OCD), and has been an ongoing experimental target for deep brain stimulation (DBS) in both rats and humans. In order to translate basic scientific results from rodents to the human setting a large animal model is needed to thoroughly study the effect of such therapeutic interventions. The aim of the study was, accordingly, to describe the basic anatomy of the Göttingen minipig NAcc and its retrograde connections. Tracing was carried out by MRI-guided stereotactic unilateral fluorogold injections in the NAcc of Göttingen minipigs. After two weeks the brains were sectioned and subsequently stained with Nissl-, autometallographic (AMG) development of myelin, and DARPP-32 and calbindin immunohistochemistry. The minipig NAcc was divided in a central core and an outer medial, ventral and lateral shell. We confirmed the NAcc to be a large and well-segregated structure towards its medial, ventral and lateral borders. The fluorogold tracing revealed inputs to NAcc from the medial parts of the prefrontal cortex, BA 25 (subgenual cortex), insula bilaterally, amygdala, the CA1-region of hippocampus, entorhinal cortex, subiculum, paraventricular and anterior parts of thalamus, dorsomedial parts of hypothalamus, substantia nigra, ventral tegmental area, the retrorubral field and the dorsal and median raphe nuclei. In conclusion the Göttingen minipig NAcc is a large ventral striatal structure that can be divided into a core and shell with prominent afferent connections from several subrhinal and infra-/prelimbic brain areas.